Beyond biopolitics : essays on the governance of life and death - Clough, Patricia Ticineto, 1945-; Willse, Craig, 1975- (Online access with subscription: Duke University Press., 2011)
Interdisciplinary collection of essays on the techniques of governance and economy that are used to organize populations around questions of life and death.